Articulating the Shape: Transversal Pedagogical Actions for the Construction of Knowledge on Visual Syntax (ModaPalavra e-periódico, 2020)
This paper emphasizes the development of the ability to articulate the visual / formal syntax as a fundamental way for the consolidation of project thinking among fashion design students. From an exploratory approach, it integrates two research focuses: the first investigates the self-regulation of learning in project teaching; the second addresses methodological strategies for the development of the ability of compositional synthesis. Thus, the study examines practices for Visual Methodology learning in the Bachelor of Fashion Design course at the State University of Londrina, searching for effective contributions in the experimental creative manipulation and decomposition of visual messages. With that aim, a combination of pedagogical actions (assignments) is analyzed, aiming at proving its didactic efficiency. Results confirm the potential of such actions and self-regulated learning strategies as facilitators of the ability to generate expressive concepts and create artifacts in the field of fashion.
Keywords: Fashion Design; Visual Syntax; Project.